A Presynaptic Regulatory System Acts Transsynaptically via Mon1 to Regulate Glutamate Receptor Levels in Drosophila. - Deivasigamani, S.; Basargekar, A.; Shweta, K.; Sonavane, P.; Ratnaparkhi, G.S.; Ratnaparkhi, A. (Genetics, 2015)
Mon1 is an evolutionarily conserved protein involved in the conversion of Rab5 positive early endosomes to late endosomes through the recruitment of Rab7. We have identified a role for Drosophila Mon1 in regulating glutamate receptor levels at the larval neuromuscular junction. We generated mutants in Dmon1 through P-element excision. These mutants are short-lived with strong motor defects. At the synapse, the mutants show altered bouton morphology with several small supernumerary or satellite boutons surrounding a mature bouton; a significant increase in expression of GluRIIA and reduced expression of Bruchpilot. Neuronal knockdown of Dmon1 is sufficient to increase GluRIIA levels, suggesting its involvement in a presynaptic mechanism that regulates postsynaptic receptor levels. Ultrastructural analysis of mutant synapses reveals significantly smaller synaptic vesicles. Overexpression of vglut suppresses the defects in synaptic morphology and also downregulates GluRIIA levels in Dmon1 mutants, suggesting that homeostatic mechanisms are not affected in these mutants. We propose that DMon1 is part of a presynaptically regulated transsynaptic mechanism that regulates GluRIIA levels at the larval neuromuscular junction.